The Implementation of Picture Series in Teaching Narrative Writing for the Tenth Graders of SMAN 2 PONOROGO - RACHMAWATI, WAVY (RETAIN : Journal of Research in English Language Teaching, 2013)
Abstract The process of teaching learning which is still monotonously makes the students feel bored in enjoying the lesson. They cannot express and show their ability freely because they just sit and hear the teacher explanation during the class is running. This situation can make the students become passive in the class. To anticipate this situation, some teachers in different schools have found the way to raise the students’ interest and motivation in teaching learning process. It is the use of picture series. Because picture series consist of some pictures that have good appearance, so teachers expected that by using this media the students will be more motivated to follow the teaching learning process. In some cases, students often get difficulty in finding idea to write a narrative. Some experts say that probably it can be solved by giving media to them. That is picture series. This media is suitable for tenth grader because the researcher think that in this level, students of tenth grader can understand about picture series well. It can stimulate the students to comprehend the events of the story and make the students easy to write because they already have the ideas that are going to write. This study uses descriptive qualitative design. The instruments that are used by the researcher are field notes, students writing assignments, and questionnaire. Field notes are used to get the information of the implementation of picture series in the teaching learning process. Students writing assignment are used to get the information of students writing narrative ability. And questionnaires are used to get the information of students’ response toward the implementation of picture series. The result of the implementation shows that picture series which is implemented by teacher helps students in writing narrative text. They can see some interesting picture, so they can get ideas and write it easily. Teacher implements the media in four steps; they are stimulating the students according to the material, presenting the material, discussing the material, and producing narrative text. It is one of a good media to teach narrative writing text. After analyzed all the instruments, the researcher make some conclusions. As the media in teaching narrative text, the implementation of picture series conduct in several steps, they are stimulating the students according to the material, presenting the material, discussing the material and producing narrative text. It really helps the students. This study also is expected to be a helpful reference in conducting another research related to writing narrative text in the future. Key words: picture series, writing narrative text and tenth graders.